Frey operation for chronic pancreatitis associated with pancreas divisum: case report and review of the literature - Skórzewska, Magdalena; Romanowicz, Tomasz; Mielko, Jerzy; Kurylcio, Andrzej; Pertkiewicz, Jan; Zymon, Robert; Polkowski, Wojciech P. (Gastroenterology Review/Przegląd Gastroenterologiczny, 2014)
Pancreas divisum (PD) is the most common congenital anomaly of the pancreas, which increases susceptibility to recurrent pancreatitis. Usually, after failure of initial endoscopic therapies, surgical treatment combining pancreatic resection or drainage is used. The Frey procedure is used for chronic pancreatitis, but it has not been reported to be applied in an adult patient with PD-associated pancreatitis. The purpose of the paper was to describe effective treatment of this rare condition by the Frey procedure after failure of interventional endoscopic treatment. A 39-year-old female patient was initially treated for recurrent acute pancreatitis. After endoscopic diagnosis of PD, the minor duodenal papilla was incised and a plastic stent was inserted into the dorsal pancreatic duct. During the following 36 months, the patient was hospitalised several times because of recurrent episodes of pancreatitis. Thereafter, local resection of the pancreatic head combined with lateral pancreaticojejunostomy was performed with no complications. After 54 months of follow-up, the patient demonstrates abnormal glucose metabolism, with a need for enzyme supplementation, and she is free of pain. Local resection of the pancreatic head combined with lateral pancreaticojejunostomy (Frey procedure) offers a favourable outcome after failure of endoscopic papillotomy and duct stenting for pancreatitis associated with PD.